More Than Numbers: The Ways Churches Grow - Mead, Loren B. (Rowman & Littlefield Publishers, 1993)
Mead explores what church growth and evangelism really mean in a time when it is mathematically impossible for every congregation to achieve significant numerical growth. He argues provocatively that spiritual, organizational, and missional growth are just as important as numerical growth, and that all four are needed for a truly healthy and growing church. Case studies and discussion questions are included.